Ethnography of Health and Illness Behaviour in Nigeria - Adodo, Anselm (Advances in Social Sciences Research Journal, 2021)
The ineffective initiatives to tackle Nigeria's various health issues have contributed to the marginal change in health outcomes. Besides ignoring the value of tackling public health problems, it will make the situation even worse for vulnerable Nigerians that frequently remain at the wrong end. This work followed a conceptual measure to explain the targets and purpose of the work comprehensively. The study was information was sourced from the Nigerian Ministry of Health through their web search engines, rational analysis and necessary documentation. The main challenges that public health is facing in Nigeria seem to be communicable diseases, vector control on some diseases, maternal deaths, child mortality rates, improper sanitation, hygiene, disease control, non - contagious diseases, and the issue of injuries from some diseases road accidents and many more. At the moment, Nigeria is struggling to accomplish strategic development goals. However, given coordinated action by the Nigerian Government, funding organisations, including NGOs, provide healthcare efficiently and effectively in Nigeria.